Calcineurin A Is Essential in the Regulation of Asexual Development, Stress Responses and Pathogenesis in Talaromyces marneffei - Zheng, Yan-Qing; Pan, Kai-Su; Latgé, Jean-Paul; Andrianopoulos, Alex; Luo, Hong; Yan, Ru-Fan; Wei, Jin-Ying; Huang, Chun-Yang; Cao, Cun-Wei (Frontiers in Microbiology, 2020)
Talaromyces marneffei is a common cause of infection in immunocompromised patients in Southeast Asia and Southern China. The pathogenicity of T. marneffei depends on the ability of the fungus to survive the cytotoxic processes of the host immune system and grow inside host macrophages. These mechanisms that allow T. marneffei to survive macrophage-induced death are poorly understood. In this study, we examined the role of a calcineurin homolog (cnaA) from T. marneffei during growth, morphogenesis and infection. Deletion of the cnaA gene in T. marneffei resulted in a strain with significant defects in conidiation, germination, morphogenesis, cell wall integrity and resistance to various stressors. The ΔcnaA mutant showed a lower minimal inhibitory concentration (MIC) against caspofungin (16 μg/ml to 2 μg/ml) and micafungin (from 32 μg/ml to 4 μg/ml) compared with the wild-type. These results suggest that targeting calcineurin in combination with echinocandin treatment may be effective for life-threatening systemic T. marneffei infection. Importantly, the cnaA mutant was incapable of adapting to the macrophage environment in vitro and displayed virulence defects in a mouse model of invasive talaromycosis. For the first time, a role has been shown for cnaA in the morphology and pathogenicity of a dimorphic pathogenic filamentous fungus.